Legal Protection for Witnesses in The Criminal Act of Theft Based on The Criminal Code (KUHP) - Tarigan, Hendra Julianto Marselinus; Aspan, Henry; Zarzani, Riza (Fakultas Hukum Dehasen, 2026)
The crime of theft as regulated in Chapter XXII, Article 362 of the Criminal Code is theft in its basic form. The elements are, namely the